Activating Competence: Role Breadth Self-Efficacy as a Mediating Route and Work Discipline as a Direct Predictor of Employee Performance - Valencia Florentina Lumantow; Riane Johnly Pio; Johny R E Tampi (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines whether role breadth self-efficacy (RBSE), confidence in undertaking tasks beyond prescribed roles, explains the relationship between employee competence and performance, and whether work discipline contributes independently. Research Method: A two-wave census survey involved all 55 employees of a state-owned pawnbroking branch in Manado, Indonesia. Competence and work discipline were measured at Time 1, RBSE four weeks later, and immediate supervisors rated performance. Fifty-three employees completed both waves and were matched with ratings from four supervisors. Partial least squares structural equation modeling was used. Results and Discussion: Competence did not directly predict performance but predicted RBSE, which subsequently predicted supervisor-rated performance. The positive indirect effect through RBSE had a bias-corrected interval excluding zero, indicating indirect-only mediation, while work discipline retained a direct association. Thus, competence was linked to performance mainly through employees’ confidence to act beyond prescribed roles, although causality cannot be inferred. Implications: Competence development may need to be paired with involvement and task control, although no intervention was tested. Originality: RBSE is positioned as a candidate activation mechanism in Indonesian financial-service work, extending prior models emphasizing person-job fit or job satisfaction.